Following the thread of Ariadne: The University City of Coimbra as glocal heritage - Capela de Campos, Joana (2018)
This paper approaches the international connections in the architecture of the University City of Coimbra, in order to achieve its glocal heritage condition, as a platform for intersection of global and local cultures. In addition, it intends to update the contents of the CAPOCUC Fund. It also seeks to promote it through file identification by cross-referencing the data of official letters with external entities.